The Influence of Competence and Motivation on Employee Job Satisfaction at the UPT DP3AP2KB in Donggo District - Sumiyati; Jaenab; Muhammad Badar (Journal of Creative Power and Ambition (JCPA), 2026)
This study aims to analyze and determine the influence of competence and motivation, both partially and simultaneously, on employee job satisfaction at the UPT DP3AP2KB, Donggo District. This study uses multiple linear regression analysis to test the influence of competence and motivation on employee job satisfaction at the UPT DP3AP2KB and the Family Planning Extension Center, Donggo District, with all research instruments proven valid and reliable and fulfilling the classical assumption test. The results of the study indicate that competence and motivation have a positive and significant effect on job satisfaction, both partially and simultaneously, with motivation having a more dominant influence than competence. In addition, the coefficient of determination value of 93.2% indicates that variations in employee job satisfaction can be largely explained by competence and motivation, while the rest is influenced by other factors outside the study. The results of the study indicate that competence has a positive and significant effect on employee job satisfaction at the UPT DP3AP2KB, Donggo District, which means that the better the employee's abilities, knowledge, and skills, the higher the level of job satisfaction they feel. In addition, motivation is also proven to have a positive and significant effect on job satisfaction, so that employees who have high motivation tend to be more enthusiastic and feel more satisfied in carrying out their work. Thus, increasing competence and motivation becomes an important factor in efforts to increase employee job satisfaction.